Earthquake Resistant Building Structure Design Study Using Steel Plate Shear Wall System (SPSW) - Silalahi, Oktavia Ully Artha (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Multi-story building structures are vulnerable to lateral forces, especially due to forces caused by earthquakes. Because the higher the building, the greater the lateral deflection that occurs on the upper floors. Indonesia is one of the countries that has high earthquake intensity. One area that has high earthquake intensity is Yogyakarta. The structural building that will be reviewed and analyzed is a 10-story hotel. The development of science and technology has given rise to one solution to improve the performance of tall building structures, namely by installing steel plate shear walls. Steel plate shear walls are a lateral load-resisting system consisting of solid vertical steel plates connecting surrounding beams and columns that are installed along the height of the structure to form a supporting wall. Designing earthquake-resistant buildings with the addition of a steel plate shear wall system provides a suitable structural system to withstand lateral forces during an earthquake. The use of this system can be a recommendation, to be able to utilize steel material as a building structural material by considering the advantages of using the steel material within the limits of applicable regulations, ASCE 7-10 and AISC 341-10. In the analysis of the building structure, the influence of dynamic earthquake loads is reviewed using the SAP 2000 auxiliary program.